Enhanced runout and erosion by overland flow at low pressure and sub-freezing conditions: Experiments and application to Mars - Conway, S.; Lamb, M.; Balme, M.; Towner, Martin; Murray, J. (Academic Press, 2011)
We present the results of laboratory experiments to study the sediment transport and erosional capacity of water at current martian temperature and pressure. We have performed laboratory simulation experiments in which a stream of water flowed over test beds at low temperature (~−20 °C) and low pressure (~7 mbar). The slope angle was 14° and three sediment types were tested. We compared the erosive ability, runout and resulting morphologies to experiments performed at ambient terrestrial temperature (~20 °C) and pressure (~1000 mbar), and also to experiments performed under low pressure only. We observed that, as expected, water is unstable in the liquid phase at low temperature and low pressure, with boiling and freezing in competition. Despite this, our results show that water at low temperature and low pressure has an equivalent and sometimes greater erosion rate than at terrestrial temperature and pressure. Water flows faster over the sediment body under low temperature and low pressure conditions because the formation of ice below the liquid-sediment contact inhibits infiltration. Flow speed and therefore runout distance are increased. Experiments at low pressure but Earth-ambient temperature suggest that flow speeds are faster under these conditions than under Earth-ambient pressure and temperature. We hypothesise that this is due to gas bubbles, created by the boiling of the water under low atmospheric pressure, impeding liquid infiltration. We have found that both basal freezing and low pressure increase the flow propagation speed – effects not included in current models of fluvial activity on Mars. Any future modelling of water flows on Mars should consider this extra mobility and incorporate the large reduction in fluid loss through infiltration into the substrate.